NEURODEVELOPMENTAL OUTCOME IN PRETERM INFANTS - Palić, Ilija (Medicinski podmladak, 2024)
About 15 million children are born prematurely every year. Preterm delivery is the main cause of death worldwide in children less then five years old. The infants born with very low birth weight (<1500 g at birth) and infants born very preterm (<32 gestational weeks) are at high risk for neurodevelopmental disability. Three common and frequently forms of brain injury in preterm infants are intraventricular hemorrhage, white and gray brain matter injury. Motor developmental delay is early identified in premature infants, especially durig the first three years of life. The major motor deficit is cerebral palsy, but in school age minor motor dysfunction are diagnosed and named developmental coordination disorder. The second domain in which developmental delays are identified is cognitive development. Children born prematurely have lower intelligence quotient and high risk of speech and language disabilities. The low of gestational age and low birth weight are the risk factors emotional disorders, attention deficit/hyperactivity disorders and autism spectrum disorders. The frequency of visual impairment and hearing loss decreased with enlarging gestational age at birth. Intracranial hemorrhage and neonatal seizures are identified as a prominent risk factors for later onset epilepsy. A key strategy to reduce neurodevelopmental disability is prevention of preterm delivery. Transport of pregnant women with a risk of preterm delivery and delivery in tertiary centres, prenatal administration of glucocorticoids and magnesium sulphate decreasing risk of preterm brain injury and impove neurodevelopmental outcome. Also, the program "Neonatal Individualized Developmental Care and Assessment Program" and application of the "skin-to-skin contact" method (Kangaroo Mother Care) have favorable effects on the neurodevelopmental outcome in premature infants. Future research should make new recommendations for neuroprotection of the preterm infants.